Core outcomes in neonatal encephalopathy: a qualitative study with parents. Issue 1 (25th July 2022) - Quirke, Fiona; Ariff, Shabina; Battin, Malcolm; Bernard, Caitlin; Bloomfield, Frank H; Daly, Mandy; Devane, Declan; Haas, David M; Healy, Patricia; Hurley, Tim; Kibet, Vincent; Kirkham, Jamie J; et al.
Abstract : Objective: To identify the outcomes considered important to parents or caregivers of infants diagnosed with neonatal encephalopathy, hypoxic ischaemic encephalopathy or birth asphyxia in high-income and low- to middle-income countries (LMiCs), as part of the outcome-identification process in developing a core outcome set (COS) for the treatment of neonatal encephalopathy. Design: A qualitative study involving 25 semistructured interviews with parents or other family members (caregivers) of infants who were diagnosed with, and treated for, neonatal encephalopathy, hypoxic ischaemic encephalopathy or birth asphyxia. Setting: Interviews were conducted in high-income countries (HiCs) (n=11) by Zoom video conferencing software and in LMiCs (n=14) by phone or face to face. Findings: Parents identified 54 outcomes overall, which mapped to 16 outcome domains. The domains identified were neurological outcomes, respiratory outcomes, gastrointestinal outcomes, cardiovascular outcomes, motor development, cognitive development, development (psychosocial), development (special senses), cognitive development, development (speech and social), other organ outcomes, survival/living outcomes, long-term disability, hospitalisation, parent-reported outcomes and adverse events. Conclusions: This study provides insight into the outcomes that parents of infants diagnosed with neonatal encephalopathy have identified as the most important, to be considered in the process of developing a COS for the treatment of neonatal encephalopathy. We also provide description of the processes employed to ensure the inclusion of participants from LMiCs as well as HiCs.